Impediments to learning problem-solving in Malawian lower secondary mathematics textbooks - Felix K. Masina; Reidar Mosvold (AOSIS, 2023)
Background: In a culture where teachers follow the textbook prescriptively, Malawian students perform low in mathematics, and no students reach the problem-solving levels. Aim: To explore reasons for students' low performance, this study aims at investigating opportunities to learn problem-solving in Malawian mathematics textbooks. Setting: This study focuses on Malawian mathematics textbooks in the lower secondary grades focusing on the areas of linear equations and simultaneous linear equations. These areas have a particular emphasis on problem-solving. Methods: Four textbooks from two of the most widely used series of mathematics textbooks in Malawian secondary school were analysed. The Mathematics Discourse in Instruction framework was used to analyse examples and tasks in the four textbooks. Results: Analysis indicates that the textbooks provide relatively few opportunities to learn problem-solving, and most of the opportunities are given through word problems. These word problems are typically presented towards the end of the chapters, and students are thus stimulated to apply already learned procedures to solve the problems rather than learn through problem-solving. Conclusion: Limitations in opportunities to learn problem-solving are particularly challenging in a context like Malawi, where teacher-textbook compliance is high, where there is a shortage of qualified mathematics teachers and where few students have access to their own textbook. Contribution: This study provides an overview of impediments to learning problem-solving in Malawian mathematics textbook, and knowledge about such impediments is necessary for change.